2021
DOI: 10.1155/2021/3668568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol on Serum Levels of Type II Collagen and Aggrecan in Patients with Knee Osteoarthritis: A Pilot Clinical Study

Abstract: Treatment of knee osteoarthritis (OA) remains a challenging concern. Preclinical studies provided accumulating evidence on resveratrol efficacy in ameliorating degenerative articular damage. The present study was conducted to evaluate the effects of resveratrol as monotherapy on the serum level of type II collagen (Coll 2-1) and aggrecan in patients with knee osteoarthritis. The study was an open-labeled noncontrolled clinical trial. Resveratrol 500 mg/day in a single oral dose was given to the patients with k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Two recent clinical studies confirmed the involvement of resveratrol in managing knee OA pain and its associated symptoms [ 51 , 67 ]. Supplementation of 500 mg/day resveratrol led to increased aggrecan serum levels and significantly improved pain, although no significant decrease in serum levels of IL-6, IL-1β, and TNF- α was observed [ 56 ].…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 95%
See 2 more Smart Citations
“…Two recent clinical studies confirmed the involvement of resveratrol in managing knee OA pain and its associated symptoms [ 51 , 67 ]. Supplementation of 500 mg/day resveratrol led to increased aggrecan serum levels and significantly improved pain, although no significant decrease in serum levels of IL-6, IL-1β, and TNF- α was observed [ 56 ].…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 95%
“…This nutraceutical has many health-benefiting properties, including its anti-inflammatory, antioxidant, and anticancer properties. By modulating major oxidative stress signaling pathways, resveratrol has become one of the most studied nutraceuticals in managing degenerative diseases such as OA [ 51 , 52 , 54 , 55 , 56 , 57 , 67 ] ( Table 1 ).…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a further study, Marouf et al found that oral RES (500 mg/day) for 90 days significantly improved patients’ knee pain and mobility but had no significant effect on patients’ serum Col-II levels. However, due to the limitations of the trial, such as short intervention time, small sample size, and no control group, further studies are needed to confirm the results in the future ( Marouf, 2021 ). Furthermore, pain is one of the common complaints of postmenopausal women.…”
Section: Clinical Studies About Res and Its Effects In Koamentioning
confidence: 99%
“…Middle-aged and older adults are primarily affected by KOA. Secondary KOA is usually caused by a variety of joint diseases, including joint injuries, fractures, joint fractures, and joint ligament strains [ 6 8 ]. According to statistics, 3% of people in China suffer from KOA.…”
Section: Introductionmentioning
confidence: 99%